Quantifying the Impact of Biomass Burning Emissions on Major Inorganic Aerosols and Their Precursors in the U.S. Issue 21 (11th November 2017) - Souri, Amir H.; Choi, Yunsoo; Jeon, Wonbae; Kochanski, Adam K.; Diao, Lijun; Mandel, Jan; Bhave, Prakash V.; Pan, Shuai
Abstract: The primary sources for inorganic aerosols from biomass burning are rather negligible, but they are predominantly formed chemically following emission of their precursors (e.g., SO2, NH3, HO x, and NO x ). The biomass burning contributions to some of the precursors can be considerable. Accordingly, we quantify the impact of the emissions on major inorganic aerosols in April–October 2012–2014 using a regional model simulation verified by extensive surface observations throughout the U.S. Simulated CO enhancements on an hourly basis are used to classify the U.S. into weak‐moderate (5 < CO Biomass ‐CO Base < 20 ppbv) and strongly impacted periods (CO Biomass ‐CO Base > 20 ppbv). This separation not only facilitates the identification of the spatial frequency of the impact but also helps to filter out nonimpacted periods, enabling us to focus on long‐term contributions. Despite the nonlinear responses of several trace gases to emissions, we observe increases (weak‐moderate and strong) in daily surface SO4 2− (1.16 ± 0.32 and 6.57 ± 4.65 nmol/m 3 ), NO3 − (0.36 ± 0.63, 4.70 ± 7.05 nmol/m 3 ), and NH4 + (2.70 ± 0.92 and 17.82 ± 15.17 nmol/m 3 ) on a national scale. These primarily resulted from (i) increases in daily surface SO2 (0.02 ± 0.01 and 0.10 ± 0.07 ppbv), afternoon OH (1.28 ± 4.24 and 12.82 ± 23.76 ppqv), and H2 O2 (0.06 ± 0.02 and 0.10 ± 0.08 ppbv), which may have accelerated the conversion of S(IV) to S(VI), and (ii) increases in daily surface NH3 (1.08 ± 0.73 and 8.61 ± 7.73 nmol/m 3 ) and HNO3 (1.44 ± 0.48 and 7.15 ± 4.25 nmol/m 3 ), which could have produced more particle‐phase NH4 NO3 . In the West, where atmospheric moisture is limited, enhanced SO4 2− leaves less available water for NH4 NO3 to become ions. Our results suggest that the major inorganic aerosol enhancement (mass) can reach to 23% of that of the carbonaceous aerosols. Key Points: Twenty‐one month CMAQ simulation against measurements show good modeling performance in reproducing inorganic aerosols throughout the U.S. Conversion of S(IV) to S(VI) via enhancement in OH, SO2, O3, and H2 O2, and NH4 NO3 formation through increases in NH3 + HNO3, is accelerated The enhancement of secondary inorganic aerosols from biomass burning can reach to 23% of the carbonaceous enhancement